2017
DOI: 10.1590/s1678-9946201759014
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic detection of Candida albicans and Candida dubliniensis strains isolated from oral mucosa of AIDS pediatric patients

Abstract: The aim of this study was to assess a collection of yeasts to verify the presence of Candida dubliniensis among strains isolated from the oral mucosa of AIDS pediatric patients which were initially characterized as Candida albicans by the traditional phenotypic method, as well as to evaluate the main phenotypic methods used in the discrimination between the two species and confirm the identification through genotypic techniques, i.e., DNA sequencing. Twenty-nine samples of C. albicans isolated from this popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…Risk factors associated with an increased oral Candida carriage include habitual tobacco smoking, state of chronic hyperglycemia (such as in patients with prediabetes and DM), edentulism, denture‐wearing, and poor oral hygiene status . Moreover, these risk factors have also been shown to increase the risk of peri‐implant diseases .…”
Section: Discusssionmentioning
confidence: 99%
“…Risk factors associated with an increased oral Candida carriage include habitual tobacco smoking, state of chronic hyperglycemia (such as in patients with prediabetes and DM), edentulism, denture‐wearing, and poor oral hygiene status . Moreover, these risk factors have also been shown to increase the risk of peri‐implant diseases .…”
Section: Discusssionmentioning
confidence: 99%
“…In the study, six strains produced brownish and rough colonies and developed chlamydoconidia, but only two were identified as C. dubliniensis by PCR. Furthermore, one of the isolates, identified as C. dubliniensis by PCR, did not produce chlamydoconidia on tobacco agar [7].…”
Section: Discussionmentioning
confidence: 97%
“…Although several phenotypic identification systems are designed to differentiate C. dubliniensis from C. albicans, they do not allow identifying Candida africana [4]. e discrimination between these species is relevant for the understanding of their clinical importance and epidemiological role in human infections [5][6][7]. e tobacco agar allows, in most cases, the differentiation between C. dubliniensis and C. albicans; but it is not used in Colombia as a routine medium.…”
Section: Introductionmentioning
confidence: 99%
“…Moran et al [5] reported that these two species had about 96% similar gene sequences, and more than 60% are homologous. It leads to difficulties in prompt differentiation among the two species in routine laboratory tests [6] and results that may underestimate their prevalence [7]. C. dubliniensis is reported to develop stable resistance to fluconazole (an antifungal drug) upon exposure in vitro [8].…”
Section: Introductionmentioning
confidence: 99%